2023
DOI: 10.1007/s00330-022-09367-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI radiomics: non-invasive and reproducible quantification of human lung maturity

Abstract: Objectives To assess the reproducibility of radiomics features extracted from the developing lung in repeated in-vivo fetal MRI acquisitions. Methods In-vivo MRI (1.5 Tesla) scans of 30 fetuses, each including two axial and one coronal T2-weighted sequences of the whole lung with all other acquisition parameters kept constant, were retrospectively identified. Manual segmentation of the lungs was performed using ITK-Snap. One hundred radiomics features were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In contrast with that, gynecological disorders such as different cancer entities and pelvis-related diseases benefit from other imaging methods such as MRI or CT. In the current literature, not only US, but also MRI applications profit from AI assistance, for example in fetal lung texture analysis [228,229] or cervical cancer diagnosis [230]. In the following, the benefits and limitations of AI application in OB/GYN US imaging are summarized.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with that, gynecological disorders such as different cancer entities and pelvis-related diseases benefit from other imaging methods such as MRI or CT. In the current literature, not only US, but also MRI applications profit from AI assistance, for example in fetal lung texture analysis [228,229] or cervical cancer diagnosis [230]. In the following, the benefits and limitations of AI application in OB/GYN US imaging are summarized.…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of published radiomics studies focus on oncologic pathology [34]. So far, the application of radiomics in pediatric radiology is rare, generally CT and MRI being the main modalities of examination [34], observing subjects such as cancer [35][36][37], pneumonia analysis [38], or prenatal diagnostics [39]. Up to this point, radiomics has proven its usefulness in a number of studies of the respiratory system, some examples being the ability to distinguish COVID-19 from other non-COVID-19 pneumonias [40,41], attempts to diagnose idiopathic lung fibrosis [42], quantifying the risk for lung cancer [43], or the diagnosis and evaluation of severity and prognosis in COPD patients [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The requirement to obtain informed consent was waived. A part of the study cohort ( n = 29) has been previously reported in a study that did not include 2D radiomics feature analyses [ 12 ].…”
Section: Methodsmentioning
confidence: 99%